Longitudinal Study of Stressful Life Events and Daily Stressors Among Adolescents at High Risk for Psychotic Disorders - Tessner, Kevin D. (Oxford University Press, 2011)
Psychosocial stress preceding the onset or recurrence of psychotic symptoms has been identified in patients with schizophrenia; yet there is limited understanding of the effects of stress in typically developing adolescents or those who show behavioral signs of risk for schizophrenia spectrum disorders. This study examined the developmental course of symptom progression as a function of stressful life events and daily hassles in adolescents with schizotypal personality disorder (SPD), other personality disorders, or no Axis II disorder. In this prospective longitudinal study, life events and daily stressors were assessed in adolescents aged 12 to 18 years. Results revealed that adolescents with SPD and other personality disorders reported significantly greater total, independent, and undesirable life events than individuals with no Axis II disorders. Youth with SPD report daily hassles to cause more distress compared to peers. Correlational analyses and hierarchal linear regression was used to evaluate the relationship of life events and daily stressors with psychiatric symptoms measured concurrently and 1 year later. Across diagnostic groups, the incidence of independent and undesirable life events were associated with current prodromal symptoms, while the frequency of daily stressors predicted a significant increment in positive, but not negative, prodromal symptoms over time. Therefore, adolescents who report greater daily stressors exhibit an increase in prodromal symptoms over a 1 year period. Psychosocial stress has been implicated in the etiology of schizophrenia, and these findings suggest the importance of life events and daily hassles as potential risk factors in the onset of psychotic symptoms during adolescence.